Analysis of Factors Influencing the Use of Cloud Computing (Google Workspace) Among Employees of The Financial and Development Supervisory Agency - Zulfikar Suryanirta; Mirna Amirya (Journal of Governance, 2026)
This study aims to analyze the effects of Performance Expectancy, Effort Expectancy, and Social Influence on Behavioral Intention, as well as the effects of Facilitating Conditions and Behavioral Intention on Use Behavior in the use of Google Workspace at the Financial and Development Supervisory Agency (BPKP) by employing the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The study adopted an explanatory quantitative approach. Data were collected through questionnaires from 176 BPKP employees using simple random sampling and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that Performance Expectancy, Effort Expectancy, and Social Influence have positive and significant effects on Behavioral Intention. Facilitating Conditions and Behavioral Intention have positive and significant effects on Use Behavior. The coefficient of determination (R²) shows that the model explains 36.7% of the variance in Behavioral Intention and 47.2% of the variance in Use Behavior, which are categorized as moderate. These findings imply that the increased use of Google Workspace at BPKP is influenced by perceived usefulness, perceived ease of use, social support, and the availability of organizational facilitating conditions that strengthen intention and actual usage behavior. This study provides empirical contributions to the development of the UTAUT model in the context of mandatory cloud computing implementation in the public sector and offers practical recommendations for BPKP management in strengthening supervisory functions through SPBE-based digital transformation.